Acrylamide content and quality characteristics of French fries influenced by different frying methods - Adil Ahmed, Zahraa; Mohammed, Nameer Khairullah; Meor Hussin, Anis Shobirin (Functional Food Center, 2023)
Background: This study aimed to compare the effects of three different frying methods, namely air frying (AF), microwave frying (MF), and deep frying (DF) in corn oil, on the moisture and texture, as well as the content and absorption of oil, carbohydrates and acrylamide in French fries. Materials and Methods: For the DF, the fresh potatoes were fully dipped in corn oil and the oil temperature was set at 160 °C for three intervals of 3, 5, and 7 minutes. In the MF, the oil was preheated to 180 °C for three time intervals of 160, 180, and 200 seconds. The AF was set at a temperature of 170 °C for three time intervals of 8, 10, and 12 minutes, without adding oil. Results: The results showed that AF resulted in a lower acrylamide content (21.8 ppm) after 8 minutes at 170°C compared to the other frying methods. However, DF in corn oil was preferred in terms of color, flavor, and overall acceptance in the sensory evaluation of the French fries. MF resulted in the hardest French fry texture due to excessive evaporation of moisture. Conclusion: The findings suggest that AF may be a healthier option with a lower acrylamide content, while DF in corn oil may be preferred for its superior sensory characteristics.